Children's Disclosure of Physical Abuse - The Process of Disclosing and the Responses from Social Welfare Workers. Issue 3 (2nd July 2020) - Thulin, Johanna; Kjellgren, Cecilia; Nilsson, Doris
ABSTRACT: Children experiencing physical abuse by their parents are left with several difficult decisions. The present study aims at exploring the process of disclosing the abuse and the responses from social welfare workers from a child perspective, in a Swedish context. Data was obtained from in depth interviews with 15 children with a history of child physical abuse. A qualitative content analysis was conducted in order to capture the children's experiences. Disclosing abuse was described as a process including several judgements from the child. Children describe their everyday life before disclosing, with an escalation of violence making them think they have to act in order to prevent further abuse. They made several well-thought decisions and selected a trustworthy recipient. The decision to disclose was often made out of fear, but the fear could remain after the disclosure, not knowing what will happen next. Children seem to lose control over how their abuse narratives are handled after disclosing. The recipient and social welfare worker was acting but not informing or consulting the child. Children emphasize the importance of trustworthy and competent adults when disclosing physical abuse. Ethical issues and implications for practice are discussed. Practitioner messages Disclosure is to be seen as a process, including several judgements by the child. Children emphasize the importance of trustworthy and competent adults when choosing to disclose physical abuse. Social welfare workers should inform and include children in their decision making.